Melestarikan permainan tradisonal sebagai upaya mengurangi ketergantungan anak terhadap gadget - Risqiyah, Kamiliyatur (Maliki Interdisciplinary Journal, 2024)
As technology develops today, it becomes a challenge for a nation to maintain its culture. Especially in Indonesia itself, many cultures are starting to become extinct, one of which is traditional games. Traditional games are a form of local wisdom that has been passed down from generation to generation and is oriented towards children's social attitudes, because the games are mostly played in groups, so that children will be directly involved emotionally when playing with their friends. But unfortunately, nowadays traditional games are rarely played and are starting to be replaced by online games on gadgets. Therefore, in this article we will discuss the importance of preserving traditional games to reduce the level of children's dependence on gadgets.